The natural history of fetal cells in postpartum murine maternal lung and bone marrow: A two-stage phenomenon - Pritchard, Stephanie (Landes Bioscience, 2012)
During pregnancy, fetal cells cross into the maternal organs where they reside postpartum. Evidence from multiple laboratories suggests that these microchimeric fetal cells contribute to maternal tissue repair after injury. In mouse models, most injury experiments are performed during pregnancy; however, in a clinical setting most injuries or diseases occur postpartum. Therefore, experiments using animal models should be designed to address questions in the time period following delivery. In order to provide a baseline for such experiments, we analyzed the natural history of fetal cells in the postpartum maternal organs. Female C57BL/6J mice were mated to males homozygous for the enhanced green fluorescent protein gene. Fetal cells in the maternal lungs and bone marrow were identified by their green fluorescence using in a high-speed flow cytometer and their counts were compared between the lung and bone marrow. Spearman correlation analysis was used to identify relationships between the duration of time postpartum and the cell counts and ratio of live and dead cells. Our results show that fetal cells persist in these organs until at least three months postpartum in healthy female mice. We show a two-stage decline, with an initial two and a half-week rapid clearance followed by a trend of gradual decrease. Additionally, an increase in the ratio of live to dead cells within the lung over time suggests that these cells may replicate in vivo. The results presented here will inform the design of future experiments and may have implications for women’s health.